Differentiation of ring‐substituted regioisomers of amphetamine and methamphetamine by supercritical fluid chromatography. Issue 3 (8th August 2016) - Segawa, Hiroki; T. Iwata, Yuko; Yamamuro, Tadashi; Kuwayama, Kenji; Tsujikawa, Kenji; Kanamori, Tatsuyuki; Inoue, Hiroyuki
Abstract : Chromatographic differentiation of the ring‐substituted regioisomers of amphetamine (AMP) and methamphetamine (MA) was performed by supercritical fluid chromatography (SFC). The behaviour of the retention against the changes of column temperature and co‐solvent proportion was studied. The obtained information facilitated the optimization of the each regioisomer. As a result, 2‐, 3‐, and 4‐ring‐substituted analogues of AMP and MA with methyl, methoxy, fluoro, chloro, and bromo groups were separated, generally within 6 min. In addition, we found that the separation pattern of the examined regioisomers was classified into two, which depended on the electron donating/withdrawing effect of the substituent. Our results indicate that SFC could be used in forensic drug analysis for fast, reliable identification of structurally similar drugs of abuse. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Chromatographic differentation of the right‐substituted regioisomers of amphetamine (AMP) and methamphetamine (MA) was performed by supercritical fluid chromatography (SFC).Most of the ring substituted analogs separated within 5‐6 min.